Relaxamento do corpo cavernoso de coelho induzido pela fração alcaloidal F3-5 de Aspidosperma ulei Markgr - Goes Júnior, Francisco de Assis Mendes (2007)
Erectile dysfunction is a worldwide public health issue and, in spite of advances brougth by the utilization of type-5 phosphodiesterase inhibitors, there is still much interest in new treatment alternatives, especially when derived from natural products. Some investigators observed the pro-erectile effects of an alkaloidal-rich fraction from Aspidosperma ulei Markgr., named F3-5. In this study, it was evaluated the degree of relaxation induced by F3-5 on rabbit corpus cavernosum, as well as possible Pharmacological mechanisms involved, in vitro. Several experimental assays were performed, utilizing the methods of cascade tissue superfusion and isolated tissue bath. Wíth strips ot corpus cavernosum pre-contracted with phenilephrine (5µM), dose-response curves of relaxation for F3-5 papaverine and DMSO were produced. were There were also assays fo, evaluation of the effects of L-NAME, 7-NI, 000, propranolol, atropine, sildenafil and F3-5 on the relaxations mediated by sodium litroprusside, acetylcholine, isoproterenol, sildenafil and F3-S. With depolarized preparations of corpus cavernosum, in a calcium-free, potassium-rich (60 mM) medium, the effects of F3-S and DMSO on the contractions induced by the progressive increase in Ca2+ concentration (1 - 300 mM) were observed. F3-5 was capable of inducing complete relaxation of rabbit corpus cavernosum with magnitude similar to that of papaverine for all doses tested, except 3 mg, when ít presented a significantly higher relaxation. Superfusions of L-NAME, 7-NI and ODQ did not significantly inhibit the relaxatíons provoked by F3-5, suggesting that it acts independently of the nitrergiê pathway. Propranolol and atropine also did not significantly interfere with relaxations mediated by F3-5 indicating that B-adrenergic or rnuscarinic receptors also might not be involved. F3-5 did not significantly amplify the relaxations promoted by sodium nitroprusside or acetylcholine, as opposed to sildenafil, suggesting that it does not act through inhibition of type-5 ohosphodiesterase. Finally, in cavernous tissue pre-incubated with F3-5, the minimum dose of Ca2+ necessary for muscular contraction was thirty times superior to that utilizedon the tissue without previous treatment, or treated with OMSO. This inhibition of the contractions of corpus cavernosum mediated by Ca2+ suggests, therefore, that F3-S can act through blockade of voltage-dependent calcium channels.